Pengaruh Model Probing Prompting Terhadap Keaktifan Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas XI SMK N 1 Laguboti Tahun Ajaran 2022/2023 - Sortauli Pasaribu; Pestaria Naibaho; Masniar H Sitorus; Malani Simanungkalit; Meditatio Situmorang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This study aims to determine the level of tendency of the Probing Prompting Model and the level of tendency of PAK Learning Activity of grade XI students of SMK Negeri 1 Laguboti in the 2023/2024 academic year, as well as to determine the existence of a positive and significant influence between the Probing Prompting Model on the Learning Activity of Christian Religious Education and Budi Pekerti of grade XI students of SMK N 1 Laguboti in the 2023/2024 academic year The hypothesis of this study is: There is a positive and significant effect of the Probing Prompting Model on the Learning Activity of Christian Religious Education and Ethics of grade XI students of SMK Negeri 1 Laguboti in the 2023/2024 Learning Year. This type of research is an inferential descriptive quantitative method. The population in this study were all XI students of SMK Negeri 1 Laguboti in the 2023/2024 Learning Year who were Protestant Christians totaling 198 people and the sample was taken 25% of 196 people, totaling 48 people. The instrument of this research is a closed questionnaire. The result of a simple linear equation is Y = 36.9 + 0.608x. The t test results show the value of tcount = 2.753 and ttable = 1.679, so it can be obtained tcount = 2.753> ttable = 1.679. Furthermore, data analysis for hypothesis testing with the f test obtained the value of Fhitung> Ftabel (5.94> 3.20) so it can be concluded that the hypothesis is accepted and based on the results of the coefficient of determination obtained the magnitude of the influence of the Probing Prompting model on the activeness of learning Christian Religious Education and Budi Pekerti Class XI students of SMK Negeri 1 Laguboti School Year 2023/2024 is 14.13% and another 85.87% is obtained from other inherent factors that are not examined in this study.